Analisis Antrian pada Loket Pembuatan Elektronik KTP dengan Menggunakan Simulasi Promodel - riri cornellia (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2018)
E-KTP or Electronic KTP is a population document that contains a system of security / control both in terms of administration or information technology based on the National population database. Kelurahan is one of the places visited by residents to make the E-KTP. But the high enthusiasm of the population to renew their KTPs, problems arose. The problem that occurs is a long queue occurs in several regions. Lack of information dissemination between officers and residents and systematic scheduling to the community resulting in services being less effective. The results of the data and analysis studies that have been carried out using Student Version 6.0 can be found that the pattern of population arrivals is Poisson distribution while the service time is exponentially distributed. The simulation output of utility level models from service facilities with the average percentage of teller utilities is 62.55% and the average waiting time of 12.71 minutes per person. Therefore it can be concluded that the queuing system that is long enough and the utility is low in the Kelurahan makes the services obtained by the population not optimal. Supposedly by increasing the queue window, systematic scheduling, and supporting facilities such as counseling the latest services can help overcome the duration of the population queuing. So that the proposal for the improvement of the system is very intended for Kebon Pala Village, in order to improve the quality of services that are more adequate so that residents feel satisfied with the service facilities provided and can minimize the time in line.